PTPN14, a target gene of miR‐4295, restricts the growth and invasion of osteosarcoma cells through inactivation of YAP1 signalling. (25th March 2020) - Liang, Gaofeng; Duan, Chaopeng; He, June; Ma, Wei; Dai, Xing
Abstract: Non‐receptor tyrosine phosphatase 14 (PTPN14) has emerged as a novel tumour‐suppressor in a wide range of human cancer types. However, the role of PTPN14 in osteosarcoma remains undetermined. In the present study, we aimed to explore the expression pattern, biological function, and regulation of PTPN14 in osteosarcoma. Low PTPN14 expression levels were detected in osteosarcoma cells, and PTPN14 overexpression markedly decreased the proliferation, colony formation, and invasive potential of osteosarcoma cells. Bioinformatics analysis predicted PTPN14 as a potential target gene of microRNA‐4295 (miR‐4295), and this prediction was validated by a dual‐luciferase reporter assay. PTPN14 expression was negatively modulated by miR‐4295 in osteosarcoma cells. Moreover, PTPN14 expression was inversely correlated with miR‐4295 expression in osteosarcoma tissues. Notably, miR‐4295 inhibition significantly restricted the proliferation and invasion of osteosarcoma cells. PTPN14 overexpression or miR‐4295 inhibition increased the phosphorylation of Yes‐associated protein 1 (YAP1) and impeded YAP1 nuclear translocation, leading to inhibition of YAP1‐mediated transcriptional activity. However, the miR‐4925‐inhibition‐mediated antitumour effect was partially reversed by PTPN14 knockdown. Overall, these results demonstrate that PTPN14 is a miR‐4295 target gene and it exerts a tumour‐suppressive function in osteosarcoma cells via inactivation of YAP1. Our study uncovers a miR‐4295–PTPN14–YAP1 signalling pathway that may play a crucial role in the progression of osteosarcoma.